Effect of Glycerol Levels on the Motility and Fertility of Kampung Chicken Spermatozoa Frozen in Liquid Nitrogen - Saleh, DM; Sugiyatno, Sugiyatno (ANIMAL PRODUCTION, 2007)
The use of various levels of glycerol as a cryoprotective agent for freezing kampung chicken semen was examined with respect to intravaginal insemination.  There was a significant (P<0.05) effect of various levels of glycerol (4, 8, 12 and 16 %) on motile spermatozoa, but there was no significant effect on fertility.  It was concluded that the use of glycerol for preservation of kampung chicken semen in liquid nitrogen gave satisfactory cryopreservative results on    motility of thawed kampung chicken spermatozoa, but failed to produce fertile eggs. (Animal Production 9(1): 45-48 (2007) Key Words: glycerol, kampung chicken, semen, fertility, motility, liquid nitrogen